Effective chelation of iron in beta thalassaemia with the oral chelator 1, 2-dimethyl-3-hydroxypyrid-4-one. Issue 6612 (12th December 1987) - Kontoghiorghes, G J; Aldouri, M A; Hoffbrand, A V; Barr, J; Wonke, B; Kourouclaris, T; Sheppard, L
Abstract : The main iron chelator used for transfusional iron overload is desferrioxamine, which is expensive, has toxic side effects, and has to be given subcutaneously. An orally active iron chelator is therefore required. The effects of oral 1, 2-dimethyl-3-hydroxypyrid-4-one on urinary iron excretion were studied in eight patients who had received multiple transfusions: four had myelodysplasia and four beta thalassaemia major. Different daily doses of the drug up to 100 mg/kg/day, alone or in combination with ascorbic acid, were used. In three patients with thalassaemia the effect of the drug was compared with that of subcutaneous desferrioxamine at the same daily dose. In all eight patients a single dose of oral 1, 2-dimethyl-3-hydroxypyrid-4-one resulted in substantial urinary iron excretion, mainly in the first 12 hours. Urinary iron excretion increased with the dose and with the degree of iron loading of the patient. Giving two or three divided doses over 24 hours resulted in higher urinary iron excretion than a single dose of the same amount over the same time. In most patients coadministration of oral ascorbic acid further increased urinary iron excretion. 1, 2-Dimethyl-3-hydroxypyrid-4-one caused similar iron excretion to that achieved with subcutaneous desferrioxamine at a comparable dose. In some cases the iron excretion was sufficiently high (maximum 99 mg/day) to suggest that a negative iron balance could be easily achieved with these protocols in patients receiving regular transfusions. No evidence of toxicity was observed on thorough clinical examination or haematological and biochemical testing in any of the patients. None of the patients had any symptoms that could be ascribed to the drug. These results suggest that the oral chelator 1, 2-dimethyl-3-hydroxypyrid-4-one is as effective as subcutaneous desferrioxamine in increasing urinary iron excretion in patients loaded with iron. Its cheap synthesis, oral activity, and lack of obvious toxicity at effective doses suggest that it should be developed quickly and thoroughly tested for the management of transfusional iron overload.